Double enzymatic hydrolysis preparation of heme from goose blood and microencapsulation to promote its stability and absorption. (15th February 2017) - Wang, Baowei; Cheng, Fansheng; Gao, Shun; Ge, Wenhua; Zhang, Mingai
Highlights: Neutrase and alkaline protease were used for heme extraction from goose blood. Goose blood heme was microencapsulated using vacuum freeze drying method. Effects of microencapsulated goose blood hydrolysate (MGBH) intake for IDA rats were investigated. MGBH exhibited favorable stability and availability. Abstract: Iron deficiency anemia (IDA) is the most common nutritional deficiency worldwide. This deficiency could be solved by preparing stable, edible, and absorbable iron food ingredients using environmentally friendly methods. This study investigated enzymatic hydrolysis and microencapsulation process of goose blood. The physicochemical properties, stabilities of the microencapsulated goose blood hydrolysate (MGBH) and a supplement for rats with IDA were also evaluated. The results showed that the synergetic hydrolytic action of neutrase and alkaline protease significantly increased the heme-releasing efficiency. The heme was then microencapsulated using sodium caseinate, maltodextrin and carboxymethyl cellulose (CMC) as the edible wall material, and the encapsulation efficiency of the product reached 98.64%. Meanwhile, favorable thermal, storage and light stabilities were observed for the microencapsulation. It was found that MGBH can significantly improve the body weight and hematological parameters of IDA Wistar rat.